GENERATE REPORT CRITICAL DATA IN BRI SARIWANGI PARSING TECHNIQUE USING - Aneu Yulianeu (LPPM STMIK DCI, 2017)
In line with the development of information technology, the computer also increases the ability to help resolve problems in shared areas, including in the banking sector with the thorny problems of reporting Unused clustered, random data pembenahannya take a long time and then processed again into the parts which can be read in various branches of Bank Rakyat Indonesia wherever located. The system is designed to improve the effectiveness of a critical reading of the report that deal with both the problems of semi-structured or unstructured.Bank Rakyat Indonesia engaged in the financial cycle requires prompt reporting including reporting black list, reporting the rest of loan registration, reporting IPTW smoothly, IPTW Autumn, and loan maturity. Reporting - reporting on critical data is data that is sent to the center by a particular system of the BRI branch, and then random data that has been put together it was taken again by the BRI for stacking purposes by each BRI branch.Keyword: Parsing, BRI